External Habits Formation and the Environment - Safi, Fatma (Naše gospodarstvo/Our economy, 2021)
The present paper presents a standard overlapping generations model with external habits formation and environmental quality in the utility function. Our main objective is to study the impact of external habits on capital accumula- tion and environmental quality on the intertemporal competitive equilibrium. We notice that striving for status leads to environment worsening and capital increasing when the cohort size is large.
Keywords: external habits; overlapping generations; environmental quality; utility function; capital accumulation